Should we bother doing dengue vector surveillance, and if so, how should we do it? - Williams, Craig R.; Aishah Hani Azil; Ritchie, Scott A. (Penerbit Universiti Kebangsaan Malaysia, 2019)
There is an enduring disconnect between the routine surveillance of mosquitoes that transmit dengue viruses and control activities to limit disease spread. A great variety of methods used to collect vector surveillance data exists globally, with program design typically influenced by historical, socio-cultural and cost factors. Surveillance data can be expensive to collect, meaning that without demonstration of its usefulness in directing mosquito control it may be deprioritized or even abandoned. Given that universally prescribed surveillance methods are unlikely to be sustainable and successful, we propose that strategies be designed according to the local terroir of dengue transmission. Strategy design should consider not only costs, but the amenability of workers and the public to various methods, the utility of methods for directing control and reducing disease, and the underlying spatial structure of the vector populations locally. A process of evaluating each of these factors should precede strategy design and be part of on-going review processes. In the case that the usefulness of vector surveillance cannot be demonstrated, then it may be argued that resources could be allocated to other aspects of disease control.